The Influence of Leadership on Employee Performance of PT. Actual Kencana Adhijaya Moderated by Organizational Culture - Marendra, I Gede; Fajri, Chotamul; Permatasari, Retno Japanis (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
PT. Actual Kencana Adhijaya engaged in asset assessment (appraisal) and financial management and business consulting services. The purpose of this study is to determine the partial and simultaneous influence of Leadership and Organizational Culture variables on Employee Performance using Linear Regression Analysis. In this study, the influence of the Moderating Variable (Organizational Culture) in Strengthening or Weakening the Influence of Leadership on Employee Performance. From the results of the analysis carried out, it is known that 1) Leadership has a significant influence on Employee Performance with a calculated t value (5.403)> t table (1.985). Where leadership has an influence of 23.5% on employee performance; 2) Organizational Culture has a significant influence where Organizational Culture Weakens the Influence of Leadership on Employee Performance with a calculated F value (64.874)> from F Table (3.094). Where leadership and organizational culture have an influence of 67.7%